2018
DOI: 10.1016/j.cca.2018.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serum bilirubin in southern Chinese patients with advanced nasopharyngeal carcinoma

Abstract: Pretreatment IBIL and DBIL are potentially independent prognostic factors for patients with advanced NPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Although high bilirubin has long been seen as an indicator of liver dysfunction, recent studies have confirmed that serum bilirubin has potential protective effects against various diseases, including malignant tumors, through antioxidative actions, inhibiting tumor cell proliferation and metastasis and inducing tumor cell apoptosis. [ 40 ] According to studies by Inoguchi et al, [ 41 ] bilirubin levels relate to mortality in patients with malignant tumors in a U-shaped curve, with the lowest mortality occurring at total bilirubin concentrations around 1.2mg/dL (normal range is 0.1–1mg/dL), which aligns with our findings. However, excessively high bilirubin levels can induce tumor cell apoptosis, releasing intracellular contents that can exacerbate hyperkalemia in patients, which is disadvantageous for patient survival.…”
Section: Discussionsupporting
confidence: 90%
“…Although high bilirubin has long been seen as an indicator of liver dysfunction, recent studies have confirmed that serum bilirubin has potential protective effects against various diseases, including malignant tumors, through antioxidative actions, inhibiting tumor cell proliferation and metastasis and inducing tumor cell apoptosis. [ 40 ] According to studies by Inoguchi et al, [ 41 ] bilirubin levels relate to mortality in patients with malignant tumors in a U-shaped curve, with the lowest mortality occurring at total bilirubin concentrations around 1.2mg/dL (normal range is 0.1–1mg/dL), which aligns with our findings. However, excessively high bilirubin levels can induce tumor cell apoptosis, releasing intracellular contents that can exacerbate hyperkalemia in patients, which is disadvantageous for patient survival.…”
Section: Discussionsupporting
confidence: 90%
“…27 Yao et al found that indirect bilirubin of more than 7.15 mmol/L is associated with better Progression-Free Survival/PFS (HR 0.51, 95% CI 0.36-0.72, p<0.001), OS (HR 0.60, 95% CI 0.39-0.90, p=0.012) and DMFS (HR 0.54, 95% CI 0.35-0.85, p=0.006). While direct bilirubin >2.76 mmol/L is associated with superior PFS (HR 0.60 95% CI 0.43-0.83, p=0.002) [28]. In our study, the majority of all bilirubin indexes were shown within normal limits.…”
Section: Discussionsupporting
confidence: 43%
“…In addition to vascular endothelial growth factor, the related biomarkers also include peripheral blood circulating endothelial cells. It has been found that the binding of vascular endothelial cell-specific heparin to growth factors can promote the formation of new blood vessels in vivo (20,21). The high expression of VEGF is regarded as one of the potential markers of early metastasis of nasopharyngeal carcinoma, which often indicates lymph node metastasis, recurrence, and poor prognosis of nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%